The development of Thai contemporary art and its influences: overlay memories, overlay imaging and individual spiritual identity / Ohm Pattanachoti - Pattanachoti, Ohm (Faculty of Art and Design, 2019)
This project was the creative and qualitative research aimed to develop and disseminate the information through the project and its result related to 3 key concerns consisting of; 1. To study and develop the artworks that represented the individual spiritual development. 2. To analyse the gained specific insight associated with the art practice and its relationships to the artistic creative process and the artistic learning processes. 3. To study the artworks and its influences in terms of the development of the concept related to attitude, experiences, cultural roots, and the spiritual development. The research methodology would be the combination of the review of literature and the art practice exploration alongside with its analysis and discussion within the descriptive form. Through the research finding, it could be divided into 3 crucial parts, which are namely; 1. The artistic creative process (the process of art making) 1.1 The concept and its relationships to the background and cultural roots, 1.2 The artistic forms and techniques. 2. The artistic Learning Processes 3. The symbolism in art. In conclusion, the study highlighted that through the investigation of art practice and its knowledge dissemination within the various forms of the presentations, the researcher was convinced that the study of creative process and its analysis related to self-awareness, experiences, background, and local cultural roots might lead to the understanding of artists and their concepts. On top of that, these creative processes and their findings might generate the metaphorical images of the artistic learning process that represented both the value of art and infinite artist’s spiritual identity development.